سوق الأوراق المالية في الجزائر طبيعتها معوقات نموها و متطلبات تنشيطها - zouda, ammar; boukeffa, hamza (Finance and Business Economies Review, 2018)
This study aims to investigate on the reality of the securities market in Algeria through assessing its activity and performance during the period (2007-2015), relying on a set of indexes of size and liquidity adopted in this field. Depending on the analytical descriptive approach, which allowed us to diagnose the main obstacles that prevent the development of Algiers Stock exchange, and to identify the main requirements to boost this vital market. This study is simultaneously aligned with the current trends of the Algerian government, which aims to develop the securities market as an alternative source of financing the economic development, as a result of the decline in oil prices since mid 2014 and the low level of oil revenues.